Peningkatan Kemampuan Komunikasi dan Kolaborasi dalam Pembelajaran Bahasa Inggris dengan CAPS di SMP - Wildayani, Gusti (Jurnal Didaktika Pendidikan Dasar, 2024)
The students’ lack of communication and collaboration skills motivated the researcher to find out an effective learning strategy in order to facilitate them more to improve the skills. The researcher believed that the implementation of Concept, Action, and Presentation Strategies (CAPS) enabled to overcome the problem. She carried out Classroom Action Research of Kemmis and Mc Taggart model for eight meetings at the 8th A grade, SMPN 6 Martapura in year 2023/2024. The students consisted of 31 students. Data has been collected from the results of observation for collaboration skill and students’ performance for communication skill. The research findings stated that 83.9% students has well-collaborated, 80.1% students communicated well orally, and 90.3% in written form. It has proved that the implementation of Concept, Action, and Presentation Strategy (CAPS) enabled to improve the communication and collaboration skills in English Learning.